PRETTY Mission Preparations: Steps to foster Grazing-Angle Reflectometry - Semmling, Maximilian; Li, Weiqiang; Hoque, Mohammed Mainul; Wickert, Jens; Cardellach, Estel; Dielacher, Andreas; Nahavandchi, Hossein (2023)
For the ESA mission PRETTY a three-unit cubesat is foreseen to be launched in March 2023. The satellite is designed for a low earth orbit (LEO) with a high inclination (97.66°), a low orbit excentricity and a mean orbit height of 564 km. The satellite layout comprises two scientific payloads: A passive reflectometer to acquire Earth-reflected signals of Global Navigation Satellite Systems (GNSS) and novel dosimeters to measure the Total Ionizing Dose (TID). This presentation concentrates on the preparation of the GNSS reflectometer measurements (reflectometry) for altimetric application over the global ocean and cryosphere. Reflectometry data from satellites have been used earlier for altimetric retrievals: over sea-ice [1], over the Caribbean [2] and the Seas of Indonesia [3]. The TDS-1 satellite mission and the CYGNSS constellation of reflectometry satellites were important milestones in this respect. A crucial challenge for the altimetric application of reflectometry is the retrieval of precise observations over the global oceans. High precision in GNSS is achieved observing the carrier phase delay. Respective retrievals in reflectometry reach centimeter level precision, resolving sea surface topography [4]. This precise information, however, is lost over rough ocean areas due to the dominance of diffuse scatter and the absence of coherent reflection, see limitation in [2]. Group delay observations persist under diffuse scatter conditions. However, limits in code bandwidth and group delay sampling of the previous space-borne scenarios provided only meter-level precision (tracking error) [3]. The surface roughness and the observation geometry play an important role for the altimetric application. Reflectometry satellites often acquire signals in a near-nadir geometry (seen from the receiver) that corresponds to high elevation angles at the specular surface point (usually > 45°). High elevation angles imply a high altimetric sensitivity, however, they also imply a high sensitivity to surface roughness [5]. ...